Zinc supplementation improves glycemic control for diabetes prevention and management: a systematic review and meta-analysis of randomized controlled trials. Issue 1 (4th June 2019) - Wang, Xinhui; Wu, Wenhui; Zheng, Wanru; Fang, Xuexian; Chen, Liyun; Rink, Lothar; Min, Junxia; Wang, Fudi
ABSTRACT: Background: Although many studies have shown that low zinc status is associated with diabetes, the putative effects of zinc supplementation on glycemic control are inconclusive. Objectives: The aim of this meta-analysis of randomized controlled trials was to assess the effects of zinc supplementation in preventing and managing diabetes. Methods: PubMed, Embase, and the Cochrane Library were searched for articles that were published through February 10, 2019 and contained estimates for the outcomes of interest. The pooled results were then analyzed with the use of a random-effects model. Results: Thirty-two placebo-controlled interventions were extracted from 36 publications, involving a total of 1700 participants in 14 countries. Overall, compared with their respective control groups, the subjects in the zinc-supplementation group had a statistically significant reduction in fasting glucose [FG, weighted mean difference (WMD): −14.15 mg/dL; 95% CI: −17.36, −10.93 mg/dL], 2-h postprandial glucose (WMD: −36.85 mg/dL; 95% CI: −62.05, −11.65 mg/dL), fasting insulin (WMD: −1.82 mU/L; 95% CI: −3.10, −0.54 mU/L), homeostasis model assessment for insulin resistance (WMD: −0.73; 95% CI: −1.22, −0.24), glycated hemoglobin (WMD: −0.55%; 95% CI: −0.84, −0.27%), and high-sensitivity C-reactive protein (WMD: −1.31 mg/L; 95% CI: −2.05, −0.56 mg/L) concentrations. Moreover, subgroup analyses revealed that the effects of zinc supplementation on FG are significantly influenced by diabetic status and the formulation of the zinc supplement. Conclusions: Our analysis revealed that several key glycemic indicators are significantly reduced by zinc supplementation, particularly the FG in subjects with diabetes and in subjects who received an inorganic zinc supplement. Together, these findings support the notion that zinc supplementation may have clinical potential as an adjunct therapy for preventing or managing diabetes. This trial was registered at PROSPERO as CRD42018111838.